Ревизия материалов по морфологии и экологии ксилофильиых личинок ктырей трибы Laphriini (Diptera, Asilidae). Сообщение I. Род Choerades Walk - Кривошеина, Н.П.; Мамаев, Б.М. (Вестник зоологии, 1975)
The work is devoted to the xylophyllic larvae of assassin flies developing in the galleries of various arborivorous insects. The assassin fly larvae being active predators are of an essential significance as entomophages. The data concerning the morphology and trophic relations of the larvae from 5 species of the Choerades Walk. genus as well as additional information on little known larvae of this genus are presented for the first time. The identification keys are compiled.